2005
DOI: 10.1002/app.22382
|View full text |Cite
|
Sign up to set email alerts
|

Poly(ethylene terephthalate) nanocomposite fibers by in situ polymerization: The thermomechanical properties and morphology

Abstract: A series of nanocomposites of poly(ethylene terephthalate) (PET) with the organoclay dodecyltriphenylphosphonium-mica (C 12 PPh-mica) were synthesized with the in situ polymerization method. PET hybrid fibers with various organoclay concentrations were melt-spun at various draw ratios (DRs) to produce monofilaments. The thermomechanical properties and morphologies of the PET hybrid fibers were characterized with differential scanning calorimetry, thermogravimetric analysis, wide-angle X-ray diffraction, electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 51 publications
1
27
0
Order By: Relevance
“…Bizarria et al [4] reported that mechanical properties of PET/organoclay nanocomposites were superior to that of the recycled PET in terms of strength and elasticity modulus. Chang et al [2] produced and characterized PETorganoclay dodecyltriphenylphosphonium-mica hybrid fibers. They found that the strengths of the fibers increased up to a critical clay loading and then properties decreased above that critical clay concentration.…”
Section: Crystallization Kinetics and Morphology Of Melt Spun Poly(etmentioning
confidence: 99%
See 2 more Smart Citations
“…Bizarria et al [4] reported that mechanical properties of PET/organoclay nanocomposites were superior to that of the recycled PET in terms of strength and elasticity modulus. Chang et al [2] produced and characterized PETorganoclay dodecyltriphenylphosphonium-mica hybrid fibers. They found that the strengths of the fibers increased up to a critical clay loading and then properties decreased above that critical clay concentration.…”
Section: Crystallization Kinetics and Morphology Of Melt Spun Poly(etmentioning
confidence: 99%
“…The isothermal crystallization kinetics was analyzed by evaluating degree of crystalline conversion as a function of time at a constant temperature. The relative crystallinity at different crystallization time X(t), was obtained from the ratio of the area of the exotherm up to time t divided by the total exotherm given by Equation (2), where Q t and Q % are the heat generated at time t and infinite time, respectively, and dh/dt is the heat flow rate [25]. Assuming that the relative crystallinity increases as a function of time, timedependent relative crystallinity X(t) was estimated by Avrami Equation (3).…”
Section: Differential Scanning Calorimetry (Dsc)mentioning
confidence: 99%
See 1 more Smart Citation
“…It is found that the microwave process improves the dispersion and the thermal stability of nanocomposites due to the interaction of the microwave radiation. However, in situ polymerization has become the main procedure for the preparation of nanocomposites due to its versatility and compatibility with reactive monomers [22], as well as permitting the control of the polymer and the composite structures. This method relies on the swelling of the organically modified LDHs by the monomer, followed by in situ polymerization initiated thermally or by addition of a suitable compound (catalyst) [19].…”
Section: +mentioning
confidence: 99%
“…The last method is still the most cost effective, simple, feasible and environmentally benign process for the mass production of polymeric nanocomposite (Burgentzle´ et al, 2004;Modestia et al, 2007). Considerable efforts have been devoted to improve various physical, mechanical and barrier properties of PET through mixing it with nanoclays (Phang et al, 2004;Chang et al, 2004;Chang et al, 2005;Jawahar et al, 2005). The layered clays used are mica, fluoro-mica, hectorite, saponite, etc., but one of the most commercially interesting clay is bentonite belonging to a structural family known as the 2:1 phyllosilicates (Calcagno et al, 2007).…”
Section: Bulk Modification Of Synthetic Textiles Using Nanomaterialsmentioning
confidence: 99%